Supplementary file to: Partridge, H., Haidn, I., Weech, T., Connaway, L.S., and Seadle, M. (2014) The Researcher Librarian Partnership: building a culture of research, Library and Information Research, 38(118), 35-51. (2014) - Partridge, H.; Haidn, I.; Weech, T.; Connaway, L.S.; Seadle, M.
No abstract available